Chitosan as Chelating and Protective Agents from Lead Intoxication in Rat - Marianti, Aditya; Anatiasara, Debi; Ashar, Fachrudyn Faisal (Biosaintifika: Journal of Biology & Biology Education, 2017)
Increasing accumulation of lead in body causes serious health problems. Chelation is widely used to decrease lead level in body. This research aims the effectivity of chitosan in chelating lead and their protective ability toward liver and kidney for lead acetate-induced rat. Thirty rats were divided into 6 treatment groups. All groups, except control group, were administered by 175 mgkg-1 BW lead acetate. Positive control group was treated using EDTA 50 mgkg-1 BW. Treatment group 1,2, and 3 were treated using chitosan in dose of 64, 32, and 16 mgkg-1 BW dissolved in 2% acetic acid, respectively in 30 days. The effectivity of chitosan was compared to blood lead level. ALT and AST level were measured to determine the protective ability of chitosan. Normal function of kidney was assessed using creatinine level. Results showed that blood lead level from all treatment groups, except negative control group, had no significant difference from control group. EDTA and chitosan ability in chelating lead were proven by low level of AST, ALT, and creatinine in treatment groups. This indicated that there was no significant difference from control group. Chitosan capable of chelating lead and protecting kidney and liver from heavy metal.